The Regulation of Medical Device Representatives: A Question of Trust? - Bernadette Richards; Susannah Sage Jacobson; Mianna Lotz; Wendy Rogers (Law, Technology and Humans, 2022)
The introduction of new technologies in medical treatment has led to innovation in medical devices that are highly technical in their application and operation. The medical technology landscape is changeable and healthcare providers often turn to the medical device representatives (MDRs), employed by device manufacturers to help navigate the shifts and uncertainties. While the relationship between MDRs and healthcare providers can be a positive one focusing on appropriate use, selection and safety of devices, it is one that has evolved over time and is not independently regulated. In addition, patients, for the most part, are usually unaware of the involvement of MDRs in their healthcare. It is this knowledge gap with regard to the role of MDRs that is the focus of this paper.